SOFT EXPERT *pg SET - Albinaa, T.A. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In the present paper, we explore a class of sets namely soft *pre generalized closed sets in expert soft topological spaces and obtain their characterizations